2016
DOI: 10.1007/s10554-016-1045-3
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial mechanics strongly predict functional capacity assessed by cardiopulmonary exercise testing in subjects without structural heart disease

Abstract: Left atrium function is essential for cardiovascular performance and is evaluable by two-dimensional speckle-tracking echocardiography (2D-STE). Our aim was to determine how echocardiographic parameters interrelate with exercise capacity and ventilatory efficiency in subjects with no structural heart disease. Asymptomatic volunteers, in sinus rhythm and with normal biventricular size and function, were recruited from a community-based population. Individuals with moderate-to-severe valvular disease, pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
0
18
2
Order By: Relevance
“…In the current study we demonstrated a limited role of atrial performance on outcomes in Fontan patients. These results are in strong contrast to results in a similarly sized group of healthy adults, in which atrial function assessed by echocardiography strongly predicted exercise performance [15].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the current study we demonstrated a limited role of atrial performance on outcomes in Fontan patients. These results are in strong contrast to results in a similarly sized group of healthy adults, in which atrial function assessed by echocardiography strongly predicted exercise performance [15].…”
Section: Discussioncontrasting
confidence: 99%
“…The atria play an important role in diastole and during exercise atrial function might be augmented [14]. Atrial function assessed by echocardiographic strain has been shown to predict exercise capacity in healthy adults [15]. A predictive value of atrial function on exercise performance has also been confirmed in patients with dilated cardiomyopathy [16], heart failure with preserved ejection fraction [17], and tetralogy of Fallot [18].…”
Section: Introductionmentioning
confidence: 99%
“…LV GLS was proved to be a strong marker of LV functional status, 34,35 and LA passive EF may be perceived as a composite marker of LV diastolic function, LA stiffness, and filling pressures, which may explain their predictive value. 36,37 Previous studies using cardiac magnetic resonance examinations in athletes observed strong correlations between cardiac size and cardiopulmonary fitness. 5,38 In parallel with our results, more pronounced LV and LA morphologic remodeling was found to be associated with better exercise capacity in echocardiographic studies as well.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the management of patients with AS is based on the assessment of AS severity, left ventricular ejection fraction (LVEF), and symptom development [2]. In patients with aortic valve disease, the left atrium (LA) undergoes remodeling due to pressure overload, resulting in disturbances in three functional phases: reservoir, conduit, and contractile phase [3, 4]. In patients with AS, there is an increase in filling pressures and LA afterload, due to left ventricular (LV) hypertrophy.…”
Section: Introductionmentioning
confidence: 99%